Research on Clay Mineral Expansion Inhibition in Coalbed Methane Mining Based on XRD Analysis and Drilling Fluid Performance Optimization - Wang, Xinman; Zhang, Fei; Cheng, Lu; Wang, Yibing; Cao, Chao; Lai, Peng; Yang, Qi (International Journal of Natural Resources and Environmental Studies, 2025)
Coalbed methane (CBM) is one of the crucial energy sources in China. The swelling of clay mineral components in coal can lead to wellbore instability and reduced coal permeability, posing challenges during drilling operations. To address these issues, analyzing and detecting the mineral components in coal and selecting inhibitors for drilling fluids that can suppress the hydration and swelling of clay minerals are vital. X-ray diffraction (XRD) analysis is employed to determine the mineral composition of coal samples, providing data for reservoir evaluation. Furthermore, coal swelling experiments are conducted to select optimal inhibitors for drilling fluids. The results indicate that potassium chloride effectively inhibits the hydration and swelling of clay minerals in coal. When coal rocks are soaked in drilling fluid containing potassium chloride for 16 hours, the coal swelling rate remains below 0.3%. Therefore, potassium chloride can be used as a drilling fluid additive at drilling sites to enhance coal permeability and achieve efficient CBM extraction.